Brain Perfusion Alterations on 3D Pseudocontinuous Arterial Spin-Labeling MR Imaging in Patients with Autoimmune Encephalitis: A Case Series and Literature Review - Li, R.; Jin, S.; Wang, Y.; Li, J.-F.; Xiao, H.-F.; Wang, Y.-L.; Ma, L. (American Journal of Neuroradiology, 2022)
SUMMARY: Autoimmune encephalitis is a heterogeneous group of newly identified disorders that are being diagnosed with increasing frequency. Early recognition and treatment of autoimmune encephalitis are crucial for patients, but diagnosis remains challenging and time-consuming. In this retrospective case series, we describe the findings of conventional MR imaging and 3D pseudocontinuous arterial spin-labeling in patients with autoimmune encephalitis confirmed by antibody testing. All patients with autoimmune encephalitis showed increased CBF in the affected area, even when some of them presented with normal or slightly abnormal findings on conventional MR imaging. Additionally, serial 3D pseudocontinuous arterial spin-labeling showed perfusion reduction in 1 patient after therapy. For patients with highly suspected autoimmune encephalitis, 3D pseudocontinuous arterial spin-labeling may be added to the clinical work-up. Further studies and longitudinal data are needed to corroborate whether and to what extent 3D pseudocontinuous arterial spin-labeling improves the diagnostic work-up in patients with autoimmune encephalitis compared with conventional MR imaging.AEautoimmune encephalitisASLarterial spin-labeling3D pCASL3D pseudocontinuous arterial spin-labelingMELASmitochondrial encephalopathy with lactic acidosis and strokelike episodesrCBFrelative CBF